MODELLING OF POST-INJECTION STRATEGIES OF ETHANOL AND EXPERIMENTAL ANALYSIS OF THE USE OF ETHANOL IN THE FORM OF DUAL FUEL AND EMULSION IN DIESEL ENGINE - Gurbuz, Huseyin; Sandalci, Tarkan (VINCA INST NUCLEAR SCI, 2021)
In this research, as the first stage, the effects of the ethanol on engine performance and emissions under the fumigation and emulsion method were experimentally investigated under part load and various engine speed conditions. Diesel-ethanol blend containing 5% ethanol by volume was used as the mixture fuel. In the fumigation method, ethanol was used at the same rate and 99.9% purity as the emulsion method. As the second stage, the effects of ethanol post injection on engine performance and pollutant emissions were investigated in the experimental engine modeled in AVL Boost simulation program and compared with the experimental results. Simulation post injection tests were performed separately after the main injection at 3 degrees CA (P1) and 7 degrees CA (P2). In the experimental studies, NOx emission decreased with the emulsion method (E5) at low and high engine speeds. In post injection strategies, NOx emission in general increased due to improved combustion and increased in-cylinder temperature with P1 (first post injection) and P2 (second post injection) strategies. Soot emission decreased significantly with E5. This improvement in soot emissions was approximately 87% in post injection strategies.
Keywords: ethanol emulsion; fumigation; dual fuel combustion; post injection; emissions; Diesel engine; BIODIESEL; PERFORMANCE; COMBUSTION; EMISSION; BLENDS; REACTIVITY; IMPACT; NOX; Thermodynamics